ChemInform Abstract: A Simple Metal‐Free Synthesis of 2, 4, 5‐Trisubstituted Pyridines and Pyridine N‐Oxides by [2 + 2] Cycloaddition of Enaminones to Propyne Iminium Salts. Issue 1 (January 2015) - Bezensek, Jure; Prek, Benjamin; Groselj, Uros; Golobic, Amalija; Stare, Katarina; Svete, Jurij; Kantlehner, Willi; Maas, Gerhard; Stanovnik, Branko
Abstract A simple, metal‐free method for the synthesis of the title pyridines is developed, which complements the existing methods of 2‐pyridine synthesis by coupling reactions of organometallic reagents.